2019
DOI: 10.1097/prs.0000000000006046
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles from Human Adipose-Derived Stem Cells for the Improvement of Angiogenesis and Fat-Grafting Application

Abstract: Background: The efficacy of autologous fat transplantation is reduced by fat absorption and fibrosis that are closely related to unsatisfactory vascularization. Extracellular vesicles are key components of the cell secretome, which can mirror the functional and molecular characteristics of their parental cells. Growing evidence has revealed that adipose-derived mesenchymal stem cells have the ability to enhance vascularization, which is partly ascribed to extracellular vesicles. The authors evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 47 publications
1
64
0
2
Order By: Relevance
“…ASCs, which can be obtained from adipose tissue, have been experimentally shown to have angiogenic and adipogenic characteristics [18]. In light of these functions, and because graft retention is mainly due to tissue regeneration, many studies have focused on the long-term retention of ASCs-assisted lipotransfer [14,19,20]. However, consisitent with the results of Paik and Natsuko's research [16,17], we also found that the concentrations of ASCs in adipose tissue in uences the rate of retention.…”
Section: Discussionmentioning
confidence: 99%
“…ASCs, which can be obtained from adipose tissue, have been experimentally shown to have angiogenic and adipogenic characteristics [18]. In light of these functions, and because graft retention is mainly due to tissue regeneration, many studies have focused on the long-term retention of ASCs-assisted lipotransfer [14,19,20]. However, consisitent with the results of Paik and Natsuko's research [16,17], we also found that the concentrations of ASCs in adipose tissue in uences the rate of retention.…”
Section: Discussionmentioning
confidence: 99%
“…Mesenchymal cell graft into the sovrachoroidal space should promote a continuous incretion of GFs that are capable of interfering with the evolution of RP in several ways: Antioxidant, antinflammatory, antiapoptotic, citoprotective, and hemorheological activities [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…Mesenchymal cell graft into the sovrachoroidal space promotes a continuous incretion of GFs that are capable of interfering with the evolution of RP in several ways [46,47].…”
Section: Discussionmentioning
confidence: 99%